Analisis Buku Ajar Biologi SMA Kelas XI Materi Sistem Peredaran Darah dan Sistem Endokrin - Ranti An Nisaa; Maesaroh Maesaroh (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
The majority of textbooks are used as the main source of learning in the classroom. The National Education Standards Agency and the Book Center require that every textbook has met certain standards that it has set in accordance with the needs, curriculum, and developments in science and technology. The purpose of the study was to determine the suitability of the material on the circulatory system and endocrine system in biology textbooks with the demands of competence in the curriculum. This study uses a descriptive method with a qualitative approach. The results showed that the material on the circulatory system and endocrine system was sufficient to meet the Basic Competencies (KD) contained in the curriculum and in accordance with the standards of the National Education Standards Agency (BSNP). There are some inaccuracies in the material presented. In the material on the endocrine system, several deficiencies were found in the presentation of concepts such as the explanation of the hormones ADH, FSH, LH, the pancreas gland, the thymus gland, and abnormalities due to certain hormone deficiencies. There are three typos, and in the supporting image there is a lack of image clarity and color.